EVALUASI HUKUM TERHADAP EKSISTENSI KETETAPAN MPR SECARA NORMATIF KONSTITUSIONAL DALAM RANGKA MENGAWAL TEGAKNYA KONSTITUSI NEGARA - Malik Ibrahim (Journal of Law ( Jurnal Ilmu Hukum ), 2013)
Politics of Law none other than policy of law which not only will form and enforce law which written and organize as positive law, however also which must confess as single law which is have highest status. At Annual Conference of MPR in the year 2003, MPR specify Decision Of MPR RI Number of I/Mpr/2003 about Sighting to Items and Status Punish Decision of MPRS and Decision Of MPR RI since year 1960 up to year 2002. Target of forming of Decision of the MPR is to evaluate status and items punish each Decision of MPRS and Decision of MPR, specifying existence of Decision of MPRS and Decision of MPR to in this time and a period of to come, and also to give rule of law and Constitutional rights of citizen. Before Code Number 12 in the year 2011, and type of hierarchy law and regulation arranged in Code Number 10 in the year 2004 about Forming of Law And Regulation. In Section 7 sentence (1), wherein him do not the including Decision Of MPR. UU No. 12 in the year 2011 about Forming of Law And Regulation replaced in arranging law and regulation massage under Constitution and above Code/regulation of government of substitution of code (Perpu) so that peep out consequence punish in system legislation of us. On the contrary, entry of Decision of MPR in and type of hierarchy law and regulation exactly bear problem of new law, that is opposition between Rule Section 4 Decision Of MPR Number of I/Mpr/2003 Section 7 sentence (1) Code Number 12 in the year 2011.